2017
DOI: 10.1155/2017/5184790
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Fragility Estimates of LRB Base Isolated Frames Using Performance-Based Design

Abstract: With improving technology, the idea of using energy dissipater equipment has been strengthened in order to control the structures response in dynamic loads such as wind and earthquake. In this research, we dealt with seismic performance of base isolated structures with lead-rubber bearing (LRB) using incremental dynamic analysis (IDA). For this purpose, 3- and 9-story buildings have been utilized in the SAC project undergoing 22 earthquake records which were far-fault. Plotting the fragility curve for various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
1
11
1
Order By: Relevance
“…In addition, another useful and more convenient tool for designers who deal with design and assessment of marine structures subjected to probabilistic loadings is fragility curves [26]. After performing preliminary analysis to attain the IEA data, the fragility curves can be extracted to anticipate whether the structure has exceeded a certain limit state such as general buckling limit state or the occurrence of multiple buckling mode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, another useful and more convenient tool for designers who deal with design and assessment of marine structures subjected to probabilistic loadings is fragility curves [26]. After performing preliminary analysis to attain the IEA data, the fragility curves can be extracted to anticipate whether the structure has exceeded a certain limit state such as general buckling limit state or the occurrence of multiple buckling mode.…”
Section: Resultsmentioning
confidence: 99%
“…A relatively similar concept called incremental dynamic analysis (IDA) has been established in recent years in order to assess the performance of the building and fixed offshore structures subjected to seismic loading (see, e.g., [18][19][20][21][22][23][24][25]). Mansouri et al [26] implemented the IDA method 3 on several-story buildings to analyze the damping effect of the lead-rubber bearing on the seismic performance of base isolated structures and represented the fragility curves to study the annual exceedance probability of some limit states. Based on the IDA, relatively novel methodologies have been proposed by some researchers for environmental loads other than earthquakes, such as Incremental Wave Analysis (IWA), Endurance Wave Analysis (EWA), and Incremental Wind Wave Analysis (IWWA) (Golafshani et al [27], Zeinoddini [28]).…”
Section: Introductionmentioning
confidence: 99%
“…Seismic probabilistic risk assessment aims to determine the probability distribution of the frequency of adverse consequences due to the potential effects of the earthquake [25,26]. The probabilistic analysis of seismic demand is a method to estimate the mean annual frequency of the exceeding limit state and hazard demand.…”
Section: Probabilistic Seismic Analysis 21 Demand and Capacity Factor Design (Dcfd)mentioning
confidence: 99%
“…Vamvatsikos et al developed and applied the incremental dynamic analysis to predict collapse under the effect of scaled earthquake records [5]. Mansouri et al conducted the seismic fragility analysis for 3-and 9-story base-isolated buildings [6]. It was found that the installation of the isolation layer decreased the amount of failure probability.…”
Section: Introductionmentioning
confidence: 99%